Dioscin Alleviates Crystalline Silica-Induced Pulmonary Inflammation and Fibrosis through Promoting Alveolar Macrophage Autophagy - Du, Sitong (Theranostics, 2019)
Occupational exposure to crystalline silica (CS) particles leads to silicosis, which is characterized by chronic inflammation and abnormal tissue repair. Alveolar macrophages (AMs) play a crucial role in the process of silicosis. Previously, we demonstrated positive effect of dioscin on silicosis through modulating macrophage-elicited innate immune response. However, the concrete molecular mechanism remains to be discovered. Methods: We established experimental model of silicosis with wildtype and Atg5(flox/flox)Dppa3(Cre/+) mice and oral administrated dioscin daily to explore the effects of dioscin on macrophages and pulmonary fibrosis. AM cell line MH-S with Atg5 silence was used to explore specific function of dioscin on macrophage-derived inflammation and the underlying molecular mechanism. Results: Dioscin could promote autophagy in macrophages. Dioscin-triggered AMs autophagy limited mitochondrial reactive oxygen species (mtROS) mass stimulated by CS, reduced mitochondria-dependent apoptosis pathway activation and facilitated cell survival. Relieved oxidative stress resulted in decreased secretion of inflammatory factors and chemokines. Dioscin treatment alleviated macrophage-derived inflammation and subsequent abnormal collagen repair. All the dioscin's protective effects were diminished in Atg5(flox/flox)Dppa3(Cre/+) mice. Conclusion: Dioscin promoting autophagy leads to reduced CS-induced mitochondria-dependent apoptosis and cytokine production in AMs, which may provide concrete molecular mechanism for the therapy of silicosis.